Strontium isotope evidence for Pre-Islamic cotton cultivation in Arabia - Ryan, Saskia E.; Douville, Eric; Dapoigny, Arnaud; Deschamps, Pierre; Battesti, Vincent; Guihou, Abel; Lebon, Matthieu; Rohmer, Jérôme; Dabrowski, Vladimir; Dal Prà, Patricia; Nehmé, Laïla; Zazzo, Antoine; et al. (Frontiers in Earth Science, 2023)
With a view to understanding the dynamics of ancient trade and agrobiodiversity, archaeobotanical remains provide a means of tracing the trajectories of certain agricultural commodities. A prime example is cotton in Arabia, a plant that is non-native but has been found in raw seed and processed textile form at Hegra and Dadan, in the region of al-‘Ulā, north-western Saudi Arabia - sites of critical importance given their role in the trans-Arabian trading routes during Antiquity. Here, we demonstrate that the measurement of strontium isotopes from pre-cleaned archaeological cotton is methodologically sound and is an informative addition to the study of ancient plant/textile provenance, in this case, putting forward evidence for local production of cotton in oasis agrosystems and possible external supply. The presence of locally-grown cotton at these sites from the late 1st c. BCE – mid 6th c. CE is significant as it demonstrates that cotton cultivation in Arabia was a Pre-Islamic socio-technical feat, while imported cotton highlights the dynamism of trade at that time.